Pendidikan Kewarganegaraan Untuk Menciptakan Generasi Berkarakter - Alfakih Anggi Subekti; Fatahillah Dhea Aanaqoh; Virgiandika Miransya; Oky Setiawan; Ilham Hudi (LPPM Politeknik Pratama, 2024)
Citizenship education aims to cultivate citizens who not only possess good academic abilities but also have strong social awareness and are capable of actively participating in community life. This is achieved by instilling values ​​of democracy, human rights, and citizenship responsibility. In this study, a qualitative approach was used to analyze texts and descriptive data from relevant literature to assess the importance of citizenship education in building responsible and honest character. The results indicate that citizenship education involves understanding of political and legal systems as well as the formation of positive attitudes, values, and morals in individuals. Therefore, the next generation is expected to have strong character and contribute positively to society. Thus, this research highlights the importance of citizenship education in preparing individuals to be active, responsible citizens who play a role in building inclusive and democratic societies